Understanding vaccine hesitancy in COVID-19 - Trogen, Brit; Pirofski, Liise-anne (Med (New York, N.Y. : Online), 2021)
Vaccines are one of the greatest medical innovations of all time, but there has been skepticism about them throughout history. Although initial concerns about scarcity increased public demand for COVID-19 vaccines, as supply meets demand, vaccine hesitancy may become a defining theme of the next stage of the COVID-19 pandemic. Vaccines are one of the greatest medical innovations of all time, but there has been skepticism about them throughout history. Although initial concerns about scarcity increased public demand for COVID-19 vaccines, as supply meets demand, vaccine hesitancy may become a defining theme of the next stage of the COVID-19 pandemic.